Pengaruh Kompetensi dan Lingkungan Kerja terhadap Kinerja dengan Motivasi sebagai Variabel Moderating pada Pegawai Puskesmas Rambah Hilir II - Resti Rahayu; Seprini Seprini; Arfianti Novita Anwar (Jurnal Ilmiah Universitas Batanghari Jambi, 2026)
This study aims to further demonstrate the influence of competence, work environment, and motivation on employee performance. The population in this study were employees of the Rambah Hilir II Community Health Center in Rokan Hulu Regency. The sample size was determined at 44 employees. This sample size was determined based on a saturation (census) technique. The independent variables in this study were competence and work environment, the mediating variable was motivation, and the dependent variable was employee performance. Data collection techniques used were observation, questionnaires, and interviews. Data analysis used Structural Equating Modeling (SEM PLS) and Smart PLS. The results showed that competence had a positive and significant effect on employee performance, work environment had a positive and significant effect on employee performance, competence had no significant effect on motivation, work environment had no significant effect on motivation, motivation had a positive and significant effect on employee performance, competence had a significant effect on performance through employee work motivation, and work environment had a significant effect on performance through employee work motivation.